Tindak Pidana Penipuan Multi-Level Marketing (MLM): Studi Komparatif KUHP dan UU Perlindungan Konsumen - Sudawan, Muhammad Yuda; Mukti, Robby Teja; Al-Huda , Mukhlis (Postulat, 2025)
This research analyzes the criminal act of fraud within Multi-Level Marketing (MLM) schemes through a comparative study between the Indonesian Criminal Code (KUHP) and Law No. 8 of 1999 concerning Consumer Protection (UUPK). MLM as a modern marketing strategy is often misused by pyramid scheme practices that focus on recruiting new members and harming the public. The criminal law framework through the KUHP and consumer protection through the UUPK play roles in addressing MLM-related fraud but face implementation challenges. This research also highlights weaknesses in the Trade Law regarding the definition of pyramid schemes that can be exploited. This study employs a qualitative approach with a normative legal framework, analyzing primary data (laws and regulations) and secondary data (legal literature). Qualitative analysis indicates that the KUHP (Article 378) is effective in prosecuting individual perpetrators by proving fraudulent intent, while the UUPK provides broader protection against misleading business practices and advertising by business actors, as well as providing compensation mechanisms for consumers. The KUHP and UUPK are complementary, but the structural eradication of pyramid schemes is hampered by definitional loopholes in the Trade Law. Revisions to trade regulations and enhanced coordination in law enforcement and public literacy are needed to comprehensively address this issue.